It S the Christian Democrats Fault: Declining Political Identification in Chile, 1957-2012 - Osorio-Flores, R (Cambridge University Press, 2015)
For different reasons, identification with political parties has been on the decline everywhere. Using polling data, we show that political identification in Chile increased in times of polarization before 1973 and in the transition to democracy in 1990 and fell under democratic consolidation. The decline comes primarily from falling identification with the largest party, the centrist Christian Democratic Party (PDC). Assessing the determinants of party identification, we report that while in the 1960s the PDC had a wide appeal as it attracted voters identified with the left, centre and right, in recent years the PDC attracts support from centrists and older people. Copyright © Canadian Political Science Association (l Association canadienne de science politique) and/et la Société québécoise de science politique 2016.